2015
DOI: 10.1002/2014jd022611
|View full text |Cite
|
Sign up to set email alerts
|

Climatic controls on the interannual to decadal variability in Saudi Arabian dust activity: Toward the development of a seasonal dust prediction model

Abstract: The observed climatic controls on springtime and summertime Saudi Arabian dust activities during 1975-2012 are analyzed, leading to development of a seasonal dust prediction model. According to empirical orthogonal function analysis, dust storm frequency exhibits a dominantly homogeneous pattern across Saudi Arabia, with distinct interannual and decadal variability. The previously identified positive trend in remotely sensed aerosol optical depth since 2000 is shown to be a segment of the decadal oscillation i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
142
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 131 publications
(155 citation statements)
references
References 84 publications
13
142
0
Order By: Relevance
“…Previous studies have shown that there are decreases in dust from South America over the 1990-2005 period in some models (Doney et al, 2009), but these are not shown in all the model versions or supported by robust observational data (Doney et al, 2009). Yu et al (2015) show evidence for strong decadal variability in the Saudi Arabian source over a different time period than considered here, with an increase between 2000 and 2015, arguing that a drought in the Fertile Crescent is (Fig. 9), consistent with their results, and correlation between precipitation and dust source in these simulations (Table 7).…”
Section: Modeled Temporal Trends In Different Regionssupporting
confidence: 79%
See 1 more Smart Citation
“…Previous studies have shown that there are decreases in dust from South America over the 1990-2005 period in some models (Doney et al, 2009), but these are not shown in all the model versions or supported by robust observational data (Doney et al, 2009). Yu et al (2015) show evidence for strong decadal variability in the Saudi Arabian source over a different time period than considered here, with an increase between 2000 and 2015, arguing that a drought in the Fertile Crescent is (Fig. 9), consistent with their results, and correlation between precipitation and dust source in these simulations (Table 7).…”
Section: Modeled Temporal Trends In Different Regionssupporting
confidence: 79%
“…It is well established in the dust literature that meteorology and surface conditions play central roles in driving changes in dust emissions, primarily from changes in precipitation, winds, surface roughness or vegetation cover on daily to interannual to geological timescales (e.g., Westphal et al, 1987;Petit et al, 1999;Marticorena and Bergametti, 1996;Mahowald et al, 2002;Prospero and Lamb, 2003;Engelstadter and Washington, 2007;Engelstaedter et al, 2003;Roe, 2008;McGee et al, 2010;Knippertz and Todd, 2012;Cowie et al, 2013;Yu et al, 2015), and we do not seek to repeat or review that work here. Rather, we address the question of how sensitive our simulation of interannual variability is to the meteorology or, alternatively, the modeling framework used.…”
Section: Introductionmentioning
confidence: 99%
“…A substantial increase in AOD over the Middle East since the onset of the 21st century has been revealed from various remote-sensing and ground-based observations Klingmüller et al, 2016;Notaro et al, 2015;Yu et al, 2015) and has been reproduced by global aerosol models (Chin et al, 2014). A substantial increase in AOD over the Middle East since the onset of the 21st century has been revealed from various remote-sensing and ground-based observations Klingmüller et al, 2016;Notaro et al, 2015;Yu et al, 2015) and has been reproduced by global aerosol models (Chin et al, 2014).…”
Section: Introductionmentioning
confidence: 94%
“…Meanwhile, decadal variability is regulated by the North African rainfall and the Sahel vegetation (which activates the transport of African dust), in addition to the Mediterranean Sea surface temperatures (which activate the Shamal wind). Furthermore, Yu et al (2015) explain that there is a decreasing amount of rainfall during the winter-to-spring La Niña across the Rub' al Khali Desert, which enhances dust activity, while a relatively cool tropical Indian Ocean produces an anomalously anticyclonic circulation over the central Arabian Peninsula, which enhances the Shamal wind.…”
Section: Introductionmentioning
confidence: 99%